DENTAL SPECIALTIES CENTER: FROM THE CHARACTERIZATION TO THE ASSOCIATION OF MODULATING FACTORS OF USERS' HEALTH. - Joaquim, Davide Carlos; Pereira Felipe, Letícia; Castro de Lima, Arthur; Gonzaga da Costa, Karina; Saido Balde, Mohamed; Barbosa de Sousa, Leilane; Rocha de Melo Leite, Ana Caroline (Enfermagem Atual in Derme)
Introduction: Social and economic aspects and oral health behaviors trigger oral diseases with systemic repercussions. Objective: This study aimed to characterize and associate sociodemographic and economic aspects and self-perception, habits, and behavior in the oral health of users of the Dental Specialties Center (DSC) of a municipality in Ceará. Method: This is a cross-sectional analytical observational study with a quantitative approach, conducted in 2019, with patients seen at the Regional DSC of Baturité - CE. After consent, we completed a questionnaire, drafted based on the literature and validated. Results: Of the 388 participants, 63.14% had an income of up to one minimum wage, 54.64% had good self-perception of oral health, and 61.08% brushed at least 3 times a day. An association was observed between being a patient over the age of 40 and using toothpaste, toothbrush, and other means of hygiene and having a good self-perception of oral health, brushing teeth more than twice a day, and having sought dental care 6 months earlier. Conclusion: Despite the unfavorable demographic and economic profile, the population studied showed good self-perception and adequate oral health behaviors. In addition, their socioeconomic aspects and self-perception, habits, and oral health behaviors were related to each other.